'Tuscans are different': the cognitive dimension of local asylum policymaking during the 2015 European 'refugee crisis'. Issue 3 (4th May 2022) - Pettrachin, Andrea
ABSTRACT: This article sheds light on the so-far-neglected role of decision-makers' subjective interpretations and cognitive factors in local asylum policymaking, complementing and challenging the existing literature explaining local policy responses to the 2015 European 'refugee crisis'. How and why do local decision-makers interpret the environment in which they operate? Do subjective interpretations contribute to influence local asylum policymaking, and how? To analyse these questions, the paper adopts an actor-centred approach grounded on framing and sensemaking theories and on Bevir and Rhodes' concept of 'situated agency', and it develops a methodology based on anonymous interviews and social network analysis. Such an approach is applied to the heuristic case of Tuscany, an Italian region where the local asylum policies produced during the 'crisis' cannot be convincingly explained by looking merely at structural, institutional or strategic factors. Three arguments are developed here. First, at least in situations of 'crisis', local decision-makers are not mere passive recipients of information, but active interpreters and rationalizers, whose subjective interpretations result from framing processes and several judgement heuristics. Second, these interpretations can decisively influence local migration policymaking. Third, these interpretations can be also shaped by policy outputs, meaning that local asylum policymaking processes can have important constitutive effects.